Pengaruh Perputaran Kas, Perputaran Piutang dan Perputaran Persediaan terhadap Profitabilitas : Studi Kasus pada Perusahaan Sub Sektor Otomotif yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023 - Irma Lestari; Sri Yuni; Agus Kubertein (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to evaluate the effectiveness of current asset management, specifically cash, receivables, and inventory, and its impact on a company's ability to generate profits. The study focused on companies in the automotive sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The research approach used a quantitative method with secondary data sourced from annual financial reports. The study sample included 11 companies, resulting in a total of 44 observational data sets over four years. Data analysis was performed using SPSS version 25 software to examine the relationships and influences between the study variables. The test results showed that cash management did not significantly influence profitability. This indicates that the amount of available cash does not always correlate with profit, possibly because cash funds are not optimally utilized in productive activities. Conversely, receivables management showed a negative correlation with profitability. This finding suggests that high receivables can burden cash flow and reduce a company's ability to generate profits. Meanwhile, inventory management has a positive and significant impact on profitability, indicating that good inventory control can support smooth production and sales, thereby increasing profits. Together, these three variables explained 68.4% of the variation in company profitability, while the remaining 31.6% was influenced by factors outside the model, such as operational efficiency, cost structure, and marketing strategy. These findings provide insights for automotive company management to prioritize inventory management and review cash and receivables policies to optimize financial performance.